Behavioral Intention Towards Automotive Products in Batam City - Renny Christiarini; Randy Setiawan; Edy Yulianto Putra (Universitas Muhammadiyah Jember, 2026)
This study is intended to analyze the influence of brand perception on behavioral intentions of automotive products in Batam City, with mediation of brand quality variables, prestige, brand identity expression, and brand image. The research approach used is not a quantitative approach, with data obtained from distributing survey questionnaires to 306 respondents who use automotive products in Batam City. Data analysis was carried out using SMARTPLS software to conduct SEM-PLS tests, in terms of testing inner and outer models. The research findings reveal that brand perception has a significant effect on brand quality, prestige, and brand identity expression. However, brand perception has not been able to influence brand image. Then, brand quality, prestige, and brand identity expression have a significant effect on behavioral intentions. This study also proves the mediation effect of brand quality variables, prestige, and brand identity expression in linking the influence of brand perception on behavioral intentions of automotive products in Batam City.